Neglected role of microelements in determining soil microbial communities and fruit micronutrients in loquat orchards - Wang, Xianting; Wang, Li; Wu, Bibo; Yuan, Zhaofeng; Zhong, Yingying; Qi, Lin; Wang, Miao; Wu, Yuping; Ge, Tida; Zhu, Zhenke (Frontiers in Microbiology, 2024)
The relationships among microelements and soil microbial communities are essential for understanding the maintenance of soil's ecological functions and their effects on fruit quality in orchards. However, these relationships have not been adequately studied, despite the importance of microelements for the growth of microorganisms and plants. To address this research gap, we investigated the relationships among microelements (K, Ca, Na, Mg, Fe, Mn, Zn, and Cu), the diversity and composition of soil microbiomes, and fruit quality in loquat orchards. We found that microelements explained more variations in microbial community structures than geographic position, basic soil properties, and macroelements, with 19.6–42.6% of bacterial, 4.3–27.7% of fungal, and 5.9–18.8% of protistan genera significantly correlated with microelements. Among the microelements, AMg and ACu were the most influential in determining the soil microbiome. The soil microbes exhibited varied threshold values for environmental breadth among the microelements, with the broadest range for AMg and the narrowest for AZn. Additionally, the microbes showed significant phylogenetic signals for all microelements, with an increasing divergence of soil microelements. The dominant community assembly shifted from homogeneous selection to stochastic, and then to heterogeneous selection. Moreover, microelements and the microbiome were the top two factors individually explaining 11.0% and 11.4% of fruit quality variation, respectively. These results highlight the importance of microelement fertilization in orchard management and provide scientific guidance for improving fruit quality.